KONFIRMASI KEBERADAAN Fasciola gigantica DAN HOSPES PERANTARA DI LINGKUNGAN PEMUKIMAN EKOSISTEM RAWA KABUPATEN HULU SUNGAI UTARA, KALIMANTAN SELATAN - Budi Hairani; Syarif Hidayat; Paisal Paisal (Vektora : Jurnal Vektor dan Reservoir Penyakit, 2018)
Fasciola Gigantica infection occurs in swamp buffalo on livestock in the swamp area of Hulu Sungai Utara District. Geographically, the livestock area is linked to the villages of Sungai Papuyu and Kalumpang Dalam by swamp water with no barrier. Such condition allows the snail as intermediate host of F. gigantica in livestock areas easily spread to residential areas and, therefore, raises the risk of transmission to humans. This study aimed to confirm the presence of F. gigantica in the cercariae form and snails in the area around the settlement of both villages. The study was an observational study of cross-sectional design, conducted in August-December 2014 . Snail sampling was conducted at the Sungai Papuyu and Kalumpang Dalam village using hand collection method. To find cercariae in the snail crushing technique was performed. Cercariae was confirmed by means of PCR to ensure they are F. gigantica in the Laboratory of Molecular Biology, Lambung Mangkurat University, Banjarbaru. The results in both villages showed 6 genera of snail, namely Pomacea, Bellamyâ , Indoplanorbis , Lymnaea , Gyraulus and Melanoides . There are 3 types of cercariae in the snails, namely Echinostome cercariae , Brevifurcate – pharyngeate cercariae and Sulcatomicrocercous cercariae. PCR shows positive samples of F. gigantica in the Echinostome cercariae form in Lymnaea and Indoplanorbis snails. This confirms the presence of F. gigantica cercariae around the settlements area and Lymnaea and Indoplanorbis snail are the first intermediate hosts.